Emily Wilde's map of the Otherlands : a novel - Fawcett, Heather (Heather M.) (Fawcett, Heather (Heather M.). Emily Wilde series, 2024)
"When mysterious faeries from other realms appear at her university, curmudgeonly professor Emily Wilde must uncover their secrets before it's too late in this second installment of the Emily Wilde series. Emily Wilde is a genius scholar of faerie folklore who just wrote the world's first comprehensive encyclopaedia of faeries. She's learned many of the secrets of the Hidden Ones on her adventures... and also from her fellow scholar and former rival Wendell Bambleby. Because Bambleby is more than infuriatingly charming. He's an exiled faerie king on the run from his murderous mother and in search of a door back to his realm. And despite Emily's feelings for Bambleby, she's not ready to accept his proposal of marriage: Loving one of the Fair Folk comes with secrets and dangers. She also has a new project to focus on: a map of the realms of faerie. While she is preparing her research, Bambleby lands her in trouble yet again, when assassins sent by his mother invade Cambridge. Now Bambleby and Emily are on another adventure, this time to the picturesque Austrian Alps, where Emily believes they may find the door to Bambleby's realm and the key to freeing him from his family's dark plans. But with new relationships for the prickly Emily to navigate and dangerous Folk lurking in every forest and hollow, Emily must unravel the mysterious workings of faerie doors and of her own heart." --